Drug interactions of tacrolimus with letermovir and azole antifungals following hematopoietic stem cell transplantation: A retrospective observational analysis - Yuri Shinogi; Toshinori Hirai; Miki Ishibashi; Kazuko Ino; Isao Tawara; Takuya Iwamoto (Wiley, 2023)
Abstract Tacrolimus interacts with letermovir and azole antifungals, whereas letermovir has nonuniform effects on the pharmacokinetics of azole antifungals. We retrospectively investigated the interaction of tacrolimus (continuous infusion) with letermovir considering co‐administered azole antifungals in adult hematopoietic stem cell transplantation patients. The extent of intraindividual variation in the ratio of tacrolimus concentration to dose normalized by body weight (C/D ratio) was investigated. The correlation between the C/D ratio and estimated glomerular filtration rate (eGFR) was analyzed. In 35 patients (795 points), the C/D ratio was higher in the tacrolimus plus letermovir period than in the tacrolimus alone period (1234.7 [566.2-2721.0] ng/mL/mg/kg vs. 564.4 [245.3-1861.3] ng/mL/mg/kg, p < .001). This trend was observed when co‐administered with azole antifungals (n = 30, 1285.5 [662.7-2506.7] ng/mL/mg/kg vs. 547.1 [245.3-1861.3] ng/mL/mg/kg, p < .001), but not without azole antifungals (n = 5, 809.9 [566.2-1573.3] ng/mL/mg/kg vs. 616.1 [350.6-979.8] ng/mL/mg/kg, p = .125). For patients co‐administered fluconazole, the tacrolimus C/D ratio increased in patients with letermovir than those without letermovir (n = 28, 1215.0 [662.7-2506.7] ng/mL/mg/kg vs. 529.9 [245.3-1654.4] ng/mL/mg/kg, p < .001). Tacrolimus C/D ratio did not correlate with eGFR under letermovir and fluconazole administrations (y = 0.1x + 1307.1, r = .008, p = .968). Close blood concentration monitoring of intravenous tacrolimus is required when patients administered letermovir and azole antifungals.